The Effects of Mechanical Preload on Transmural Differences in Mechano-Calcium-Electric Feedback in Single Cardiomyocytes: Experiments and Mathematical Models - Khokhlova, Anastasia; Konovalov, Pavel; Iribe, Gentaro; Solovyova, Olga; Katsnelson, Leonid (Frontiers in Physiology, 2020)
Transmural differences in ventricular myocardium are maintained by electromechanical coupling and mechano-calcium/mechano-electric feedback. In the present study, we experimentally investigated the influence of preload on the force characteristics of subendocardial (Endo) and subepicardial (Epi) single ventricular cardiomyocytes stretched by up to 20% from slack sarcomere length (SL) and analyzed the results with the help of mathematical modeling. Mathematical models of Endo and Epi cells, which accounted for regional heterogeneity in ionic currents, Ca2+ handling and myofilament contractile mechanisms, showed that a greater slope of the active tension-length relationship observed experimentally in Endo cardiomyocytes could be explained by greater length-dependent Ca2+ activation in Endo cells compared with Epi ones. The models also predicted that greater length dependence of Ca2+ activation in Endo cells compared to Epi ones underlies, via mechano-calcium-electric feedback, the reduction in the transmural gradient in action potential duration (APD) at a higher preload. However, the models were unable to reproduce the experimental data on a decrease of the transmural gradient in the time to peak contraction between Endo and Epi cells at longer end-diastolic SL. We hypothesize that preload-dependent changes in viscosity should be involved alongside the Frank-Starling effects to regulate the transmural gradient in length-dependent changes in the time course of contraction of Endo and Epi cardiomyocytes. Our experimental data and their analysis based on mathematical modeling give reason to believe that mechano-calcium electric feedback plays a critical role in the modulation of electrophysiological and contractile properties of myocytes across the ventricular wall.